Probit Regression Analysis to Predict the Effect of Problem-Based Learning Model and Teams Games Tournament Cooperative Learning Model toward Students’ Learning Outcomes - Ardianti, Ulfah; Marlena, Leni (Universitas Islam Negeri Raden Intan Lampung, 2020)
The study aimed to predict the chances of success from the use of the Problem-based Learning (PBL) model compared to the Teams Games Tournament (TGT) toward students’ learning outcomes. The research was conducted to the eleventh-grade students of Senior High School 106 Jakarta on the limit of algebraic function material. The data were collected through a posttest of 5 description questions. After the data had been collected, it was analyzed using probit regression which can provide more information than using just the means of two populations. The independent variable was the class and the dependent variable was the learning outcome. The class independent variable was a dummy variable with the value of